Effect of Uremia and Dialysis Modality on Mononuclear Cell Apoptosis - MARTÍN-MALO, ALEJANDRO; CARRACEDO, JULIA; RAMÍREZ, RAFAEL; RODRIGUEZ-BENOT, ALBERTO; SORIANO, SAGRARIO; RODRIGUEZ, MARIANO; ALJAMA, PEDRO (Journal of the American Society of Nephrology, 2000)
The aim of this study was to evaluate the effect of both uremia itself and hemodialysis (HD) membranes on the induction of apoptosis. Four groups of subjects were evaluated: 21 nondialyzed (Non-D) patients, 10 continuous ambulatory peritoneal dialysis (CAPD) patients, and 53 HD patients who were on hemophan, cuprophan, cellulose acetate, AN69, and polysulfone; control subjects were nine healthy volunteers. Circulating mononuclear cells were obtained before dialysis and cultured for 48 h. Mean percentage of apoptosis was analyzed by a FACScan flow cytometer using Annexin V-FITC. Cell apoptosis was increased in Non-D patients (11.5 +/- 5.5%) compared with control subjects (2.1 +/- 0.7%, P < 0.001) and CAPD patients (7. 0 +/- 5.8%, P < 0.05). In patients on HD with cuprophan, apoptosis was higher than in control subjects and Non-D and CAPD patients. In Non-D patients, apoptosis was inversely correlated with renal creatinine clearance (r = -0.62, P = 0.003). Cell apoptosis was higher in hemophan than the other HD membranes. In seven patients on hemophan, switching to polysulfone resulted in decreased apoptosis (P < 0.01). Mononuclear cell circulation through mini-dialyzers made of different types of membranes (cuprophan, hemophan, cellulose acetate, AN69, and polysulfone) prouced a significant increase in apoptosis. However, there was a marked difference in the percentage of apoptosis induced by these five membranes, being significantly increased in hemophan and cuprohan compared with the other three membranes. Similar results were obtained when whole blood from healthy donors was circulated through the mini-dialyzers, showing that mononuclear cell apoptosis was increased in hemophan and cuprophan compared with polysulfone. In conclusion, uremia and membrane characteristics may independently affect the mononuclear cell apoptosis.